Aqueous self-assembly of aromatic rod building blocks - Ryu, Ja-Hyoung; Hong, Dong-Je; Lee, Myongsoo (Chemical communications (Cambridge, England), 2008)
One of the most fascinating subjects in areas such as nanoscience and biomimetic chemistry is concerned with the construction of novel supramolecular nanoscopic architectures with well defined shapes and functions. Supramolecular assemblies of aromatic rod molecules provide a facile entry into this area. Aromatic rigid rod molecules consisting of hydrophilic flexible chains, in aqueous solution can self-assemble into a variety of supramolecular structures through mutual interactions between aromatic rod molecules and water, including hydrophobic and hydrophilic interactions and pi-pi interaction. The supramolecular architecture in water can be manipulated by variation of the shape of the rigid segments, as well as the relative volume fraction of the flexible segment. The rigid aromatic segments have significant photonic and electronic properties. The self-assembly of aromatic rod molecules in water, therefore, can provide a strategy for the construction of well-defined and stable nanometer-size structures with chemical functionalities and physical properties as advanced materials for photonic, electronic and biological applications.